Adopting Basic Principles of the United Nations Academic Impact Initiative (UNAI): Can Cultural Differences Be Predicted from Value Orientations and Globalization? - Nechtelberger, Andrea; Renner, Walter; Nechtelberger, Martin; Supeková, Soňa Chovanová; Hadjimarkou, Maria; Offurum, Chino; Ramalingam, Panchalan; Senft, Birgit; Redfern, Kylie (Frontiers in Psychology, 2017)
The United Nations Academic Impact (UNAI) Initiative has set forth ten Basic Principles for higher education. In the present study, a ten item self-report questionnaire measuring personal endorsement of these principles has been tested by self-report questionnaires with university and post-graduate students from Austria, China, Cyprus, India, Nigeria, and Slovakia (total N = 976, N = 627 female, mean age 24.7 years, s = 5.7). Starting from the assumptions of Moral Foundations Theory (MFT), we expected that personal attitudes towards the UNAI Basic Principles would be predicted by endorsement of various moral foundations as suggested by MFT and by the individual's degree of globalization. Whereas for the Austrian, Cypriot, and Nigerian sub-samples this assumption was largely confirmed, for the Chinese, Indian, and Slovak sub-samples only small amounts of the variance could be explained by regression models. All six sub-samples differed substantially with regard to their overall questionnaire responses: by five discriminant functions 83.6 % of participants were classified correctly. We conclude that implementation of UNAI principles should adhere closely to the cultural requirements of the respective society and, where necessary should be accompanied by thorough informational campaigns about UN educational goals.